2015
DOI: 10.2174/1385272819666150730214506
|View full text |Cite
|
Sign up to set email alerts
|

Bischler-Napieralski Reaction in Total Synthesis of Isoquinoline-based Natural Products. An Old Reaction, a New Application

Abstract: Bischler-Napieralski (B-N) reaction is undoubtedly one of the most powerful methodologies in organic synthesis for the construction of isoquinoline moieties as important heterocyclic compounds. It has also captured great attention in the total synthesis of naturally occurring compounds such as alkaloids, which mostly and particularly bear isoquinolines as scaffold in their structures. The present review is focused on and highlighted the applications of B-N reaction, a rather old reaction, as a decisive and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…In this context, several methods have been developed by taking advantage of electrophilic activation or controlled hydride reduction (including transition‐metal‐catalyzed hydrosilylation) as the initiation process to enable subsequent selective functionalization whilst minimizing over‐reduction. As for the initiation through electrophilic activation of amides, triflic anhydride (Tf 2 O) and phosphoryl chloride (POCl 3 ) have been utilized. For example, Huang and co‐workers have demonstrated that electrophilic activation of carboxamides by Tf 2 O results in the formation of nitrilium ion intermediates, which could be subsequently functionalized by the sequential addition of metal hydride and Grignard reagents for the α‐functionalization (Scheme A) .…”
Section: Methodsmentioning
confidence: 99%
“…In this context, several methods have been developed by taking advantage of electrophilic activation or controlled hydride reduction (including transition‐metal‐catalyzed hydrosilylation) as the initiation process to enable subsequent selective functionalization whilst minimizing over‐reduction. As for the initiation through electrophilic activation of amides, triflic anhydride (Tf 2 O) and phosphoryl chloride (POCl 3 ) have been utilized. For example, Huang and co‐workers have demonstrated that electrophilic activation of carboxamides by Tf 2 O results in the formation of nitrilium ion intermediates, which could be subsequently functionalized by the sequential addition of metal hydride and Grignard reagents for the α‐functionalization (Scheme A) .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand as we mentioned macrolides are significant natural products from structural and biological points of view. Thus, due to our interest in Wittig reaction [37,38] and in the applications of other name reactions in the total synthesis of natural products, [39][40][41][42][43][44][45][46][47] herein, we try to underscore the applications of the Wittig reaction in the total synthesis of natural products, classified as macrolide family, especially those showing biological potencies.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Due to these advantages salient features, Mitsunobu reaction have been broadly utilized as an important step (steps) in the total synthesis of several natural products and many complex organic molecules. [4] In continuation of our interest in the applications of name reactions in the total synthesis of natural products, [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] herein, we try to underscore the applications of the Mitsunobu reaction in the total synthesis of naturally occurring compounds, showing diverse biological properties.…”
Section: Introductionmentioning
confidence: 99%